Interpreting for Public Services and the Community: Towards conceptual accuracy and terminological stability - Vyzas, Theodoros (International Journal of Language, Translation and Intercultural Communication, 2025)
The aim of this article is to show that interpreting in public services is a highly important and demanding social and institutional interaction, and must be distinguished from community interpreting, which means that the term public service interpreting must be used in its own right. The theoretical framework will comprise the interactionistic model (Wadensjö 1995) and Marianacci’s model (2022) of power asymmetries between public service professionals and “clients” in institutional context. Major features of interpreting such as accuracy, fidelity, impartiality and neutrality will be approached while pragmatic and socio-cultural aspects will also be discussed. Emphasis will be placed on public service settings and the power asymmetries they generate. As public service interpreting helps to balance power relations, it is indispensable to social justice, thus it must be conducted by professional interpreters.